Pengaruh Pengalaman Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja pada PT. Tip Top Ciputat - Oki Iqbal Khair; Widia Astuti (Business Management Journal, 2021)
The purpose of this research is to find out and analyze the effect of work experience on work productivity, to know and analyze the effect of work motivation on work productivity, and to know and analyze the effect of work experience and work motivation together on employee productivity PT. Tip Top Wholesale Ciputat. The research method used by the author is a quantitative descriptive method that aims to determine the effect of two or more variables, where this approach provides a description of the problem to look for the influence between variable X1 (Work Experience) and variable X2 (Work Motivation) with variable Y (Work Productivity ) then hypothesis testing is performed to determine whether the proposed hypothesis is accepted or rejected using multiple linear regression analysis. The test used 3wqato test the research instrument is a validity test and a reliability test. Hypothesis testing using the t test (partial), F test (simultaneous), multiple linear regression analysis, correlation coefficients and determination with the help of SPSS 21 Software for Windows.From the results of the multiple regression test the constant value of 13.465 states that if there is an increase in the variable Work Experience (X1) and Work Motivation (X2) the value is 0, then the Work Productivity (Y) value is 13,465. Correlation coefficient value 0.861 means that there is a very strong relationship, the value of determination is 74.2%. Work Experience Variable partially influences and significantly affects Work Productivity with a tcount of 6.442> t table 1.664, this shows that Ho is rejected and H1 is accepted. Work Motivation Variable is partially influential and significant, this is indicated by the value of tcount 5.890> t table 1.664 with a significant value of 0.000 <0.05. This shows that Ho is rejected and H2 is accepted, meaning that the Work Motivation variable partially influences Work Productivity. So, if the value of the variable Work Motivation rises, Work Productivity will increase. Work Experience and Work Motivation simultaneously have a significant effect on Work Productivity. Based on the statistical test F (simultaneous), it can be seen that the value of Fcount 110.483> Ftable 3.09 and a significant value of 0.000 <0.05, it can be concluded that Ho is rejected and H3 is accepted, this means that Work Experience and Work Motivation simultaneously have a significant effect on Work productivity.